Pemikiran Emanasi Al-Farabi dan Nur Muhammad dan Relevansinya dengan Sains Modern dengan Asal Usul Penciptaan Alam Semesta - Muh Tabran; Muhammad Amri; Andi Aderus (STAI DDI Kota Makassar, 2026)
This study aims to integrate classical Islamic philosophy and Sufism with the findings of modern science to understand the essence of the origin of the universe. The primary focus of this study is to explore the intersection between Al-Farabi’s Theory of Emanation and the concept of Nur Muhammad with the Big Bang cosmological theory and quantum physics. The method employed is qualitative library research using a philosophical and descriptive-analytical approach to analyze primary texts and scientific data. The results reveal a strong correlation between the concept of “Singularity” in the Big Bang event and the “First Sense” in the emanation system, where both represent a single point as the source of energy for all existence. Furthermore, the phenomenon of quantum entanglement in modern physics serves as a tangible reflection of the Nur Muhammad doctrine as the primordial substance unifying all dimensions of reality. The conclusion of this study affirms that the intellectual heritage of Islam, such as the thought of Al-Farabi and the Sufi tradition, remains highly relevant as a philosophical foundation for the development of contemporary science. This integration demonstrates that there is no contradiction between faith, philosophy, and science, but rather a harmony that provides a holistic understanding of the meaning and mechanisms of the universe.